2014
DOI: 10.1016/j.amjmed.2014.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Pneumocystis jiroveci Pneumonia among Groups at Risk in HIV-negative Patients

Abstract: These estimates may be used as a guide to better target pneumocystosis prophylaxis in the groups most at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
130
1
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(146 citation statements)
references
References 30 publications
4
130
1
11
Order By: Relevance
“…In contrast to the AIDS population, PCP in HIV-negative patients typically causes fever, a rapid development of respiratory failure and poor outcomes [6,11,14]. Although the incidence of PCP infection has dramatically decreased in AIDS patients, this rate continues to grow in non-HIV immunocompromised patients with organ transplants, malignancies and connective tissue diseases [4,11,15,16].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast to the AIDS population, PCP in HIV-negative patients typically causes fever, a rapid development of respiratory failure and poor outcomes [6,11,14]. Although the incidence of PCP infection has dramatically decreased in AIDS patients, this rate continues to grow in non-HIV immunocompromised patients with organ transplants, malignancies and connective tissue diseases [4,11,15,16].…”
Section: Discussionmentioning
confidence: 97%
“…Although its incidence has recently declined in patients with AIDS due to highly active antiretroviral therapies and chemoprophylaxis for patients at risk of this severe infection, PCP is an emerging threat to immunocompromised patients without HIV infection. PCP has been reported in patients on corticosteroids or immunosuppressive medications and in patients with hematological malignancies, solid cancers, inflammatory bowel diseases, organ transplants and autoimmune diseases [1][2][3][4][5][6][7]. Glomerular disease has also become an important public health problem, with a prevalence of up to 16.9 % of chronic kidney disease (CKD) in the north of China [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, only 28 patients developed PJP, and this sample size was insufficient for multivariate analysis. Past relatively large-scale studies include a cohort study by Fillatre et al [8]. They evaluated 293 patients with various disease conditions who developed PJP; the study was conducted using the national hospital discharge database.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…However, reports of patients developing the opportunistic infection Pneumocystis jirovecii pneumonia (PJP) due to their immunocompromised state have also increased [1-7]. PJP is rare in the general population with an annual incidence of only 0.01–0.015%, but a study showed that 14.9% of PJP patients have IBD [8], and a large cohort study revealed that the incidence of PJP among IBD patients is higher than in individuals without IBD (hazard ratio [HR] 2.96, 95% confidence interval [CI] 1.75–4.29) [9]. Age (≥55 years) and use of multiple immunosuppressants, such as steroids, thiopurine, and anti-tumor necrosis factor (anti-TNF) therapy, in particular have been identified as risk factors for PJP [10].…”
Section: Introductionmentioning
confidence: 99%
“…По данным метаанализа, включавшего 529 больных ГПА, ППн развилась в 125 слу-чаев, из которых в 47% наблюдали летальный исход [18]. По мнению французских авторов, УП также относится к РЗ с высоким риском развития ППн (ОР 18,3 95% ДИ 4,9-63,4) [34]. Имеются отдельные сообщения о развитии ППн у больных микроскопическим полиангиитом [9,35].…”
Section: профилактика ппн при отдельных рз васкулитыunclassified